Upaya BPBD Melakukan Pengembangan Kapasitas Kelembagaan bagi Kelompok Siaga Bencana (KSB) dalam Meningkatkan Mitigasi Bencana Alam di Kota Padang Panjang - Adinda, Bunga Puja; Putri, Nora Eka (Lembaga Yasin AlSys, 2025)
Padang Panjang City is a region vulnerable to natural disasters such as earthquakes, landslides, and floods, necessitating structured and sustainable mitigation efforts. In response, the Regional Disaster Management Agency (BPBD) has established Kelompok Siaga Bencana (KSB, or Disaster Preparedness Groups) in each subdistrict as the frontline of disaster mitigation. However, the implementation of this program still faces various challenges, including disparities in KSB capacity, limited training, inadequate equipment and facilities, and weak inter-subdistrict coordination. This study aims to analyze BPBD’s efforts in developing the institutional capacity of KSBs and to identify the supporting and inhibiting factors in enhancing disaster mitigation in Padang Panjang City. A qualitative descriptive method was used, employing purposive sampling to select key informants, including the Head of BPBD, the Head of the Prevention and Preparedness Division, and KSB members. Data were collected through interviews and documentation and analyzed using the Miles & Huberman model: data reduction, data display, and conclusion drawing. The findings indicate that BPBD has made reasonably good efforts to strengthen institutional capacity based on the three dimensions proposed by Deborah Eade: organizational, individual, and collaborative capacity. However, limited facilities and the absence of a city-level KSB coordination forum remain major obstacles. Key supporting factors include a well-defined institutional structure and high commitment among KSB members. This study offers practical implications through recommendations for improving training quality, strengthening logistics, and establishing an inter-subdistrict coordination forum. Theoretically, it contributes to the literature on risk management and institutional development in local-level disaster mitigation.